A Study on the Factors Influencing the Happiness of Rural Elderly - Soukanya, Bounthot; Xie, Lee Wen (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aimed to investigate the relationship between social support and life satisfaction among 200 rural elderly individuals using the